Incidence of Bullous Pemphigoid After Herpes Zoster Treatment with Acyclovir: A Rare Case Report in a Rural Area - Josafat Pondang; Flora Ramona Sigit Prakoeswa (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Bullous pemphigoid is the most common autoimmune subepidermal blistering disorder, accounting for approximately 80% of subepidermal immunobullous diseases. It mainly affects elderly patients aged 60–80 years and typically presents with tense bullae, widespread pruritus, and erosive skin lesions. The disease may arise from genetic predisposition and environmental triggers, including drugs that disrupt immune tolerance to dermal–epidermal junction antigens. Objective: This case report aimed to describe the clinical features of bullous pemphigoid, its possible relationship with acyclovir use, and treatment outcomes in a rural health-care setting. Method: This study used a qualitative single case report approach based on clinical observation, patient history, physical examination, and treatment evaluation. Results: A patient developed generalized tense bullae after receiving acyclovir therapy for herpes zoster. The lesions resembled bullous pemphigoid and were suspected to be related to acyclovir-induced immunological activity and its chemical structure. Management was carried out with systemic corticosteroid therapy and supportive care. Conclusion: Acyclovir may act as a rare trigger for bullous pemphigoid. The patient showed improvement in clinical signs and symptoms after seven days of steroid treatment. This finding emphasizes the need for careful monitoring of cutaneous adverse reactions following antiviral therapy, especially in resource-limited rural clinical settings.